Penerapan Mediasi Pada Kasus Pencemaran Nama Baik Yang Dilakukan Melalui Media Sosial - Josep Linsaner Diadema; I Dewa Gede Dana Sugama (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to examine how mediation is used in defamation cases that involve social media. With a normative legal perspective, this study employs a descriptive qualitative methodology. In order to analyze the phenomena and draw conclusions, this study's analysis technique involves looking at phenomena through the lens of already-existing library sources. The study's findings demonstrate how efforts to resolve criminal cases through non-litigation methods such as penal mediation can stifle efforts to resolve cases legally, leading to the imposition of criminal penalties. Keeping in mind that the goal of updating Indonesia's national criminal code is not just to exact revenge or retaliation (retributivism), but rather to resolve or repair the effects of a conflict or crime. In addition, penal mediation as a means of settling cases outside the court (non-litigation) can be a solution to overcoming the problem of overcapacity that is commonly experienced by correctional institutions in Indonesia.